2022
DOI: 10.3390/app12084016
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Satellite Image Analysis in Oil Spill Detection

Abstract: In recent years, there has been an increasing use of satellite sensors to detect and track oil spills. The satellite bands, namely visible, short, medium infrared, and microwave radar bands, are used for this purpose. The use of satellite images is extremely valuable for oil spill analysis. With satellite images, we can identify the source of leakage and assess the extent of potential damage. However, it is not yet clear how to approach a specific leakage case methodologically. The aim of this study is the rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Given the similarity between the Oil Spill dataset and the CSIRO dataset, we adhered to the color labeling standards employed in various studies for SAR images [6,24,31], as depicted in Figure 8. Although there are emerging datasets [32,33], one of the objectives of this research is to establish a standardized color representation.…”
Section: Classificationmentioning
confidence: 99%
“…Given the similarity between the Oil Spill dataset and the CSIRO dataset, we adhered to the color labeling standards employed in various studies for SAR images [6,24,31], as depicted in Figure 8. Although there are emerging datasets [32,33], one of the objectives of this research is to establish a standardized color representation.…”
Section: Classificationmentioning
confidence: 99%
“…That is, it can be more difficult to detect leaks if the soil has an initially high percentage of moisture [4]. Previous studies conducting water leak and oil spill detection also observed it to be a suitable technology [4,34]. The use of GIS can provide the general location of the leak, with infrared technology being used for accurate leak location.…”
Section: Remote Sensing and Ir Cameramentioning
confidence: 99%
“…Most current approaches for detecting oil pollution on the water surface involve either oil spill detection on the sea surface using various remote sensing monitoring methods to detect the type and area of the oil spill [10][11][12][13], or using remote sensing images to detect the oil slick [14,15]. Zhao Dong et al [16] proposed an oil slick detection method based on multispectral remote sensing technology for sea surface oil slick detection, but the method is less effective in detecting oil slicks heavily polluted by sunlight and needs to be verified by more multispectral images.…”
Section: Introductionmentioning
confidence: 99%